Building an innovation business case (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Looking at the positives of change often leads to success on the other side, so why not think that these are times of innovation instead? In this track, our objective is to learn how to capitalize on change or an idea, and to build a successful innovation business case. Learning Objectives Learn what an innovation business case is, and how it differs from an elevator pitch and a business plan Learn what a good business case needs in order to be convincing.